2021
DOI: 10.3390/v13010075
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of Genotype 1 Hepatitis E Virus ORF4 Increases Genotype 3 HEV Viral Replication in Cell Culture

Abstract: Hepatitis E virus (HEV) can account for up to a 30% mortality rate in pregnant women, with highest incidences reported for genotype 1 (gt1) HEV. Reasons contributing to adverse maternal-fetal outcome during pregnancy in HEV-infected pregnant women remain elusive in part due to the lack of a robust tissue culture model for some strains. Open reading frame (ORF4) was discovered overlapping ORF1 in gt1 HEV whose protein expression is regulated via an IRES-like RNA element. To experimentally determine whether gt3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 59 publications
0
46
0
Order By: Relevance
“…It is only recently that optimised cell models have been developed and high HEV viral loads detected in HepG2/C3A, A549, PLC/PRF/5 and Huh-7-Lunet BLR cells [24][25][26]. Increased viral replication has also been reported in hepatoma cells expressing HEV-1 ORF4 [27]. Our group previously developed an in vitro system of HEV infection in human HepaRG cells embedded in 3D Matrigel [28].…”
Section: Introductionmentioning
confidence: 99%
“…It is only recently that optimised cell models have been developed and high HEV viral loads detected in HepG2/C3A, A549, PLC/PRF/5 and Huh-7-Lunet BLR cells [24][25][26]. Increased viral replication has also been reported in hepatoma cells expressing HEV-1 ORF4 [27]. Our group previously developed an in vitro system of HEV infection in human HepaRG cells embedded in 3D Matrigel [28].…”
Section: Introductionmentioning
confidence: 99%
“…ORF4 protein is reported to enhance the replication of HEV-1 by promoting the viral RNA-dependent RNA polymerase (RdRp) activity of ORF1 [ 35 ]. A recent report demonstrated that ORF4 provided in trans enhances the viral replication of genotype 3 HEV (HEV-3) although it does not naturally encode ORF4 in its genome [ 36 ].…”
Section: Genome and Classificationmentioning
confidence: 99%
“…An additional ORF4, spanning nt2835-3308 and overlapping with ORF1, is present in HEV-gt1 alone and its protein expression is regulated via an IRES-like RNA element (nt2701-2787). ORF4 appears to cause endoplasmic reticulum (ER) stress which may be involved in promoting viral replication [ 38 , 39 ] ( Figure 2 ). As C-terminal 19 amino acids are absent in around half of the genomes, only the N-terminal 124 amino acids of pORF4 can interact with other viral and host proteins.…”
Section: Hepatitis Ementioning
confidence: 99%
“…Other hepatitis viruses (HAV, HBV and HCV) and other HEV genotypes (HEV-gt2 and HEV-gt3) do not cause higher deaths in pregnant women [ 150 ]. Among the HEV family, HEV-gt1 alone has ORF4 which encodes a protein, pORF4 of 124 aa [ 38 , 39 ]. The encoded pORF4 by the HEV-gt1 genome interact with other viral and host proteins, enhance viral polymerase activity and promote viral replication [ 123 ].…”
Section: Proposed Hypothesis On Pathogenesis Of Mortality In Hev-infected Pregnant Womenmentioning
confidence: 99%